خزع المحفظة بالنيوديميوم: ياغ ليزر و اختلاطاته - جلول قحطان (Latakia University Journal -Medical Sciences Series, 2019)
إن تكثف المحفظة الخلفية الهام سريرياً هو أشيع الاختلاطات المتأخرة لجراحة الساد غير المختلطة وبغض النظر عن إضعافه لحدة البصر فقد يخفض تكثف المحفظة الخلفية حساسية التباين أو يسبب صعوبات البهر أو الشفع بعين واحدة، وتتضمن العلامات لتكثف المحفظة الخلفية لآلئ إلشينغ التي تنجم عن تكاثر وهجرة الخلايا الظهارية الاستوائية المتبقية وذلك على امتداد المحفظة الخلفية في منطقة التماس بين بقايا المحفظة الأمامية والمحفظة الخلفية، وهي تعطي مظهراً حويصلياً للمحفظة الخلفية وأفضل ما يظهر بالتنوير الراجع، وتليف المحفظة نتيجة الحؤول الليفي للخلايا الظهارية وهو أقل شيوعاً ويظهر عادةً أبكر مما تظهر لآلئ إلشينغ. تتضمن المعالجة تشكيل فتحة في المحفظة الخلفية بالـNd: ياغ ليزر بالتبئير الدقيق وبأقل طاقة كافية من الليزر، لكن رغم ذلك قد نواجه عدة اختلاطات مثل تنقط العدسة المزروعة، ووذمة اللطخة الكيسية، وانفصال الشبكية الشقي، وارتفاع الضغط داخل المقلة، والخلع أو تحت الخلع الخلفي للعدسة، والتهاب باطن العين المزمن. Visually significant PCO is the most common late complication of uncomplicated cataract surgery. Apart from reducing visual acuity, it may impair contrast sensitivity, cause difficulties with glare or give rise to monocular diplopia. The signs include Elschnig pearlsare caused by the proliferation and migration of residual equatorial epithelial cells along the posterior capsule at the site of apposition between the remnants of the anterior capsule and the posterior capsule. They impart a vacuolated appearance to the posterior capsule, best visualized on retroillumination. and Capsular fibrosisdue to fibrous metaplasia of epithelial cells is less common and usually appears earlier than Elschnig pearls. Treatment involves the creation of an opening in the posterior capsule, with the Nd: YAG laser withaccurate focusing and using the minimum energy required, but in spite of that, we may have many complications like Lens pitting, Cystoid macular edema, Rhegmatogenous retinal detachment, Intraocular pressure elevation, Posterior IOL subluxation or dislocation, Chronic endophthalmitis.